Cohort profile: BIOVASC-late, a prospective multicentred study of imaging and blood biomarkers of carotid plaque inflammation and risk of late vascular recurrence after non-severe stroke in Ireland. Issue 7 (19th July 2020) - McCabe, John Joseph; Giannotti, Nicola; McNulty, Jonathan; Collins, Sean; Coveney, Sarah; Murphy, Sean; Barry, Mary; Harbison, Joseph; Cronin, Simon; Williams, David; Horgan, Gillian; Dolan, Eamon; et al.
Abstract : Purpose: Inflammation is important in stroke. Anti-inflammatory therapy reduces vascular events in coronary patients. 18 F-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) identifies plaque inflammation-related metabolism. However, long-term prospective cohort studies investigating the association between carotid plaque inflammation, identified on 18 F-FDG PET and the risk of recurrent vascular events, have not yet been undertaken in patients with stroke. Participants: The Biomarkers Imaging Vulnerable Atherosclerosis in Symptomatic Carotid disease (BIOVASC) study and Dublin Carotid Atherosclerosis Study (DUCASS) are two prospective multicentred observational cohort studies, employing near-identical methodologies, which recruited 285 patients between 2008 and 2016 with non-severe stroke/transient ischaemic attack and ipsilateral carotid stenosis (50%–99%). Patients underwent coregistered carotid 18 F-FDG PET/CT angiography and phlebotomy for measurement of inflammatory cytokines. Plaque 18 F-FDG-uptake is expressed as maximum standardised uptake value (SUVmax ) and tissue-to-background ratio. The BIOVASC-Late study is a follow-up study (median 7 years) of patients recruited to the DUCASS/BIOVASC cohorts. Findings to date: We have reported that 18 F-FDG-uptake in atherosclerotic plaques of patients with symptomatic carotid stenosis predicts early recurrent stroke, independent of luminal narrowing. The incorporation of 18 F-FDG plaque uptake into a clinical prediction model also improves discrimination of early recurrent stroke, when compared with risk stratification by luminal stenosis alone. However, the relationship between 18 F-FDG-uptake and late vascular events has not been investigated to date. Future plans: The primary aim of BIOVASC-Late is to investigate the association between SUVmax in symptomatic 'culprit' carotid plaque (as a marker of systemic inflammatory atherosclerosis) and the composite outcome of any late major vascular event (recurrent ischaemic stroke, coronary event or vascular death). Secondary aims are to investigate associations between: (1) SUVmax in symptomatic plaque, and individual vascular endpoints (2) SUVmax in asymptomatic contralateral carotid plaque and SUVmax in ipsilateral symptomatic plaque (3) SUVmax in asymptomatic carotid plaque and major vascular events (4) inflammatory cytokines and vascular events.